Acylhydrazone derivative
Patent Information
- Application Number
- JP2023131317
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-10
- Publication Date
- 2025-02-21
AI Technical Summary
【0010】 本発明のアシルヒドラゾン誘導体は、太陽光エネルギーなどの光エネルギーを回収·貯蔵し、利用時には熱エネルギーとして取り出すことができるので、蓄熱材及び蓄熱方法、ならびに当該蓄熱材を用いた熱利用システムを提供することができる。 本発明のアシルヒドラゾン誘導体は光を吸収して異性化及び/又は相転移することで光エネルギーを回収·貯蔵することができる。この光エネルギーを貯蔵した本発明のアシルヒドラゾン誘導体は、外部からトリガー、例えば熱又は物理的·機械的刺激を与えることにより、貯蔵した光エネルギーを熱エネルギーとして放出し得る。 本発明のアシルヒドラゾン誘導体は、高い光変換収率、異性化後の異性体の高い熱安定性、異性化前後の両異性体の吸収帯の良好な分離を維持していることに加え、アシル側鎖の導入により結晶中の分子の動的性質が高まったことで、結晶中でも高い収率で異性化が進行する。その結果、本発明のアシルヒドラゾン誘導体は、光異性化により、優れた蓄熱効果を発揮することができ、また、エネルギーを貯蔵した状態で熱安定性を有する蓄熱材を提供することもできる。
Smart Images

Figure 2025026001000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a novel acylhydrazone derivative, its use as a heat storage material, a heat storage method using said derivative, and a heat utilization system utilizing said heat storage material. [Background technology]
[0002] Today, there is a demand for the use of solar energy, but there is a problem in that the scenes (times) in which light energy can be obtained and the scenes in which that light energy is used (or desired) do not necessarily coincide in time. For example, if the light energy of daytime sunlight could be used at any time after sunset (for example, the night of the same day, the night of the next day, etc.), utility costs could be reduced.
[0003] In recent years, technology that converts light energy such as ultraviolet light into phase change energy of a substance, stores it, and reuses it as thermal energy has begun to attract attention. For example, the solid-liquid phase transition phenomenon accompanying the photoisomerization of organic molecules is expected to be applied to heat storage materials, adhesives, etc. (Non-Patent Document 1). In particular, it has been reported that photoinduced melting of crystals (photo-induced crystal-to-liquid transition, hereafter abbreviated as PCLT) utilizing the photoisomerization of azobenzene can realize excellent heat storage properties by simultaneously utilizing latent heat and heat of isomerization (Non-Patent Documents 2 and 3).
[0004] Materials that exhibit PCLT behavior are called photoinduced phase transition materials. In order to manifest PCLT, photoresponsive molecules must have high thermal stability and photoconversion yield, as well as molecular design to promote isomerization in the crystal. Due to this background, reports of PCLT have been limited to azobenzene and some other photoresponsive molecules (Non-Patent Documents 4-6). [Prior art documents] [Non-patent literature]
[0005] [Non-Patent Document 1] Xu, W.-C.; Sun, S.; Wu, S. Photoinduced Reversible Solid-to-Liquid Transitions for Photoswitchable Materials. Angew. Chem. Int. Ed Engl. 2019, 58(29), 9712–9
Outdoor Tool2
Outdoor Tools3
Outdoor Tools 4
Direct Environment 5
Outdoor Configuration6
Direct Environment 7
Outdoor Track 8
[0006] However, existing materials have problems such as insufficient efficiency in phase change due to light energy and the inability to evaluate structural changes after the phase change. There are also problems with thermal stability in the energy storage state.
[0007] The objective of the present invention is to provide a new light-induced phase transition material that has improved phase change efficiency due to light energy and improved thermal stability in an energy storage state, and a heat storage material and heat utilization system that use the same and can collect and store light energy from sunlight and other sources and extract it as thermal energy when used. [Means for solving the problem]
[0008] Acylhydrazone derivatives are known as photoresponsive molecules, and their optical properties have been actively studied since around 2015 (Non-Patent Documents 7 and 8). The present inventors believed that the high optical switching properties of acylhydrazone derivatives could be utilized to express PCLT, and as a result of extensive research, they discovered that a novel acylhydrazone derivative with a highly flexible alkyl side chain exhibits photoinduced melting, and has improved phase change efficiency due to light energy and thermal stability in the energy storage state, thus completing the present invention.
[0009] That is, the present invention is as follows. [1] Formula (I): [ka] (In the formula, R 1 and R 2 are hydrogen or, together with the carbon atom to which they are attached, form a fused phenyl ring; R 3 is an alkyl group having 1 to 3 carbon atoms; R is an alkyl group having 1 to 9 carbon atoms or an alkenyl group having 2 to 10 carbon atoms, and these alkyl or alkenyl groups are unsubstituted or substituted with OH. An acylhydrazone derivative represented by the formula: [2] R 1 and R 2 and the carbon atom to which they are bonded form a fused phenyl ring. [3] R 3 The acylhydrazone derivative according to the above [1] or [2], wherein is methyl. [4] The acylhydrazone derivative according to any one of the above [1] to [3], wherein R is a linear alkyl group having 4 to 9 carbon atoms. [5] A method for producing the acylhydrazone derivative according to any one of the above items [1] to [4], Formula (II): [ka] with a compound of formula (III): [ka] in ethanol, methanol, 1-propanol, 2-propanol, or a mixture thereof to obtain a compound of formula (I): [ka] (In the formula, R, R1 , R 2 , and R 3 is defined in any one of the above items [1] to [4]) to obtain an acylhydrazone derivative represented by the formula (I). A method comprising: [6] A heat storage material comprising the acylhydrazone derivative according to any one of the above [1] to [4]. [7] A heat utilization system comprising the heat storage material described in [6] above. [8] The heat utilization system according to [7] above, which is a residential light energy utilization system. Effect of the Invention
[0010] The acylhydrazone derivative of the present invention can collect and store light energy such as solar energy and extract it as thermal energy when utilized, and therefore can provide a heat storage material, a heat storage method, and a heat utilization system using the heat storage material. The acylhydrazone derivative of the present invention can recover and store light energy by absorbing light and undergoing isomerization and / or phase transition. The acylhydrazone derivative of the present invention that has stored this light energy can release the stored light energy as thermal energy by applying an external trigger, such as heat or a physical or mechanical stimulus. The acylhydrazone derivative of the present invention maintains a high photoconversion yield, high thermal stability of the isomer after isomerization, and good separation of the absorption bands of both isomers before and after isomerization, and in addition, the introduction of an acyl side chain enhances the dynamic properties of the molecules in the crystal, so that isomerization proceeds with a high yield even in the crystal. As a result, the acylhydrazone derivative of the present invention can exhibit an excellent heat storage effect by photoisomerization, and can also provide a heat storage material that has thermal stability in the energy storage state. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a schematic diagram of a first embodiment of a system for recovering solar light energy in a house. [Diagram 2] FIG. 1 is a diagram showing the spectral radiation distribution of sunlight. [Diagram 3] FIG. 2 is a diagram showing the results of melting point calculated from DSC measurement of compound (a). [Figure 4] FIG. 1 shows the results of PCLT tests for S2C7, S4C7, and NC7. [Diagram 5] This is a diagram showing the 1H NMR spectrum of NC7 in deuterated dimethyl sulfoxide (DMSO-d6). In the figure, "as produced" indicates the NMR of the NC7 solution, "PS state (365 nm)" indicates the NMR of the UV-irradiated solution, and "130°C, 2 hours" indicates the NMR of the heated solution. The PS state refers to the photostationary state. [Figure 6] 1 shows the UV-visible spectrum of NC7 in DMSO-d6, in which "as produced" and "PS state (365 nm)" show the UV-visible spectrum of an NC7 solution and a UV-irradiated solution, respectively. [Figure 7] FIG. 1 shows the crystal structures of the (E)- and (Z)-forms of NC7. [Figure 8] FIG. 1 shows the PCLT behavior of (E)-form crystals of NC7. [Figure 9] This is a diagram showing the DSC curves of NC7 measured in a heating and cooling cycle. The horizontal arrows in the diagram indicate the direction of temperature change, with the temperature starting to rise from 20°C in the first heating in the first stage, followed by a temperature drop from around 120°C in the first cooling in the second stage, and then a temperature rise from around -30°C in the second heating in the third stage. [Figure 10] Schematic diagram showing the energy states of the (E)-form of NC7 crystal, and the (Z)-form of NC7 melt, glass, and crystal. The upper direction indicates a higher energy state. [Figure 11]This is a DSC curve of the (E)-form crystal of NC7 measured by heating and cooling cycles. The horizontal arrows in the figure indicate the direction of temperature change, with the temperature rising from 20°C in the first heating in the first stage, followed by a temperature drop from around 150°C in the first cooling in the second stage, followed by a temperature rise from around -30°C in the second heating in the third stage, followed by a temperature drop from around 150°C in the second cooling in the fourth stage. [Figure 12] This is a DSC curve of the (Z)-form crystal of NC7 measured by heating and cooling cycles. The horizontal arrows in the figure indicate the direction of temperature change, with the temperature rising from 20°C in the first heating in the first stage, followed by a temperature drop from around 150°C in the first cooling in the second stage, followed by a temperature rise from around -30°C in the second heating in the third stage, followed by a temperature drop from around 150°C in the second cooling in the fourth stage. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The present invention will be described in detail below with reference to the drawings where appropriate, but the present invention is not limited thereto.
[0013] (Acylhydrazone Derivative Represented by Formula (I)) R of the present invention 1 and R 2 From the viewpoint of good photoconversion yield and thermal stability, it is preferred that these be combined with the carbon atom to which they are bonded to form a fused phenyl ring.
[0014] R of the present invention 3 The alkyl group having 1 to 3 carbon atoms may be linear or branched, and examples thereof include methyl, ethyl, n-propyl, and isopropyl. Methyl is preferred from the viewpoints of good photoconversion yield and thermal stability.
[0015] The alkyl group having 1 to 9 carbon atoms in R of the present invention may be linear or branched (linear is preferred), and examples thereof include methyl, ethyl, n-propyl, or isopropyl, or linear or branched butyl, pentyl, hexyl, heptyl, octyl, or nonyl. From the viewpoints of good photoconversion yield and thermal stability, the number of carbon atoms is preferably 4 to 9, particularly preferably 7 to 9, and even more preferably 7. The alkenyl group having 2 to 10 carbon atoms for R of the present invention has one or more double bonds and may be linear or branched (linear is preferred), and examples thereof include vinyl, 1-propenyl, allyl, 1-butenyl, 2-butenyl, 3-butenyl, 1-pentenyl, 2-pentenyl, 3-pentenyl, 4-pentenyl, 1-hexenyl, 2-hexenyl, 3-hexenyl, 4-hexenyl, 5-hexenyl, and 9-decenyl. From the viewpoint of good photoconversion yield and thermal stability, the number of carbon atoms is preferably 3 to 12, particularly preferably 7 to 12, and particularly preferably 10, and 9-decenyl is particularly preferred. As the alkyl or alkenyl group substituted with OH in R of the present invention, 2-hydroxypropyl is preferred from the viewpoints of good photoconversion yield and thermal stability. In the present invention, R is preferably a linear alkyl group having 4 to 9 carbon atoms, particularly preferably n-heptyl, from the viewpoints of photoconversion yield and thermal stability.
[0016] Examples of the compound represented by formula (I) include the acylhydrazone derivatives shown in Table 1 below. In Table 1, structures N and S2 are represented by the following structural formulas:
[0017] [ka] It is expressed as:
[0018] [Table 1]
[0019] As the compound represented by the formula (I), from the viewpoints of good photoconversion yield and thermal stability, NC4, NC5, NC6, NC7, NC8 and NC9 are preferred, and NC7 is more preferred.
[0020] The acylhydrazone derivative of the present invention can be produced, for example, according to the steps shown in Scheme 1 below.
[0021] [ka] (where R 1 , R 2 , R 3 and R is as defined above in formula (I).
[0022] In step 1 of the above scheme 1, a salicylaldehyde compound represented by formula (II) (hereinafter also referred to as "compound II") and a hydrazide compound represented by formula (III) (hereinafter also referred to as "compound III") are mixed in a glass container under air atmosphere, ethanol is added, the mixture is refluxed, and reacted for 24 hours, whereby an acylhydrazone derivative represented by formula (I) can be synthesized. Examples of substitutes for ethanol include methanol, 1-propanol, and 2-propanol. A mixed solvent of two or more of these can also be used, but ethanol is preferred. The reaction can be carried out at a temperature of about 25°C to the boiling point of the solvent. The reaction is generally completed in 1 hour, but a slight improvement in yield is expected by carrying out the reaction for 24 hours, which is preferable.
[0023] Compound II and compound III are commercially available or can be prepared by known methods.
[0024] (Photoinduced phase transition materials) The acylhydrazone derivative of the present invention functions as a photoinduced phase transition material, and is capable of absorbing light and recovering and storing light energy by undergoing isomerization and / or phase transition. For example, the acylhydrazone derivative of the present invention undergoes a transition to a liquid phase at a temperature below the melting point or a partial transition to another crystalline phase (hereinafter also referred to as "crystalline phase B") by irradiating the crystalline phase (hereinafter also referred to as "crystalline phase A") at the time of production with light such as ultraviolet light. Which transition occurs depends on the molecular structure of the acylhydrazone derivative at the time of production and the temperature at the time of light irradiation, and the molten state is maintained when irradiated at a temperature above the melting point of crystalline phase B. The melt and crystalline phase B after the transition are in a higher energy state than the original crystalline phase A, which corresponds to the storage of light energy. The conversion rate by light irradiation is estimated to be 99% or more. The crystals after the transition are thermally stable, and the half-life is estimated to be several tens of days or more at room temperature.
[0025] (Heat storage material) The heat storage material of the present invention may be the acylhydrazone derivative of the present invention itself, or may be composed of two or more of the acylhydrazone derivatives of the present invention, or may contain other additives, such as a binder for increasing the strength of the thin film when it is formed, or a metal or carbon nanotube (CNT) for increasing the thermal conductivity of the thin film, together with one or more of the acylhydrazone derivatives, so long as the effect of the present invention is not impaired. In particular, a heat storage material containing two kinds of acylhydrazone derivatives is preferable in that the number of heating and cooling cycles required until the heat storage phenomenon appears is reduced. The method for producing the heat storage material of the present invention is not particularly limited, but for example, one or more of the above acylhydrazone derivatives and the above additives added as necessary can be mixed and stirred to uniformly disperse the material. This heat storage material may be used by filling it into a suitable container, for example, a capsule-shaped heat storage material container (heat storage capsule). The material of the container of such a heat storage capsule can be a plastic such as polypropylene, or a metal such as aluminum or stainless steel.
[0026] The present invention provides a heat utilization system using the acylhydrazone derivative of the present invention. Hereinafter, a residential air conditioning system (embodiment 1) will be described as an embodiment of the heat utilization system of the present invention.
[0027] (Embodiment 1) A first embodiment of a method for recovering solar light energy in a house will be described with reference to Fig. 1. The wavelength of light used as the light energy is the maximum absorption wavelength of the acylhydrazone derivative of the present invention. This wavelength may vary depending on the molecular structure, but can be easily found by measuring the absorption spectrum. A light recovery device equipped with the heat storage material of the present invention receives sunlight and recovers light energy from the sun. The energy stored in the heat storage material is then released at any time to heat cooling water or to use the heat as heat needed for living and life. [Effect] is reduction in utility costs. This system is particularly effective in places with low temperatures and strong ultraviolet illuminance, such as high altitudes, polar regions, and facilities outside the stratosphere, because it absorbs ultraviolet light energy well when the absorption maximum wavelength of the acylhydrazone derivative of the present invention is in the ultraviolet wavelength region. EXAMPLES
[0028] The present invention will be described in detail below with reference to examples, but these examples are not intended to limit the present invention.
[0029] [Example 1] (S2C7 manufacturing) 2-Methoxybenzaldehyde (R 1 , R 2 H, R 3 Ga-CH 3 Compound II, wherein R is -CH 2 (CH 2 ) 5 CH 3 S2C7 was synthesized by mixing S2C7 and S2C8 in a glass container under air atmosphere, adding ethanol, refluxing the mixture, and reacting for 24 hours.
[0030] [ka]
[0031] [Example 2] Manufacturing of NC7 2-Methoxy-1-naphthaldehyde is reacted with compound III, where R is -CH 2 (CH 2 ) 5 CH 3 NC7 was synthesized by mixing NC100 and NC200 in a glass container under air, adding ethanol, refluxing the mixture, and reacting for 24 hours.
[0032] [ka]
[0033] [Example 3] (NC10en manufacturing) 2-Methoxy-1-naphthaldehyde is reacted with compound III, where R is -CH 2 (CH 2 ) 7 CH=CH 2 NC10en was synthesized by mixing NC10en and NC10en-1000 in a glass container under air atmosphere, adding ethanol, refluxing the mixture, and reacting for 24 hours.
[0034] [ka]
[0035] [Example 4] (Production of NC3OH) 2-Methoxy-1-naphthaldehyde is reacted with compound III, where R is -CH 2 CH(OH)CH 3 NC3OH was synthesized by mixing 1,2-dichlorophenyl ether (COOH) and 1,2-dichlorophenyl ether (COOH) in a glass container under air, adding ethanol, refluxing the mixture, and reacting for 24 hours.
[0036] [ka]
[0037] [Example 5] Manufacturing of NC4, NC5, NC6, NC8, and NC9 According to the method of Example 2, R is -CH2 (CH 2 ) 5 CH 3 In place of compound III, R is -CH 2 (CH 2 ) 2 CH 3 Compound III, where R is -CH 2 (CH 2 ) 3 CH 3 Compound III, where R is -CH 2 (CH 2 ) 4 CH 3 Compound III, where R is -CH 2 (CH 2 ) 6 CH 3 and R is -CH 2 (CH 2 ) 7 CH 3 Compound III was used to prepare NC4, NC5, NC6, NC8, and NC9.
[0038] [Comparative Example 1] Manufacturing of S4C7 4-Methoxybenzaldehyde is reacted with compound III, where R is -CH 2 (CH 2 ) 5 CH 3 (which is a stoichiometric formula) was mixed in a glass container under air, ethanol was added, and the mixture was refluxed and reacted for 24 hours to synthesize S4C7.
[0039] [ka]
[0040] [Test Example 1] Differential scanning calorimeter (DSC) measurements In the present invention, DSC measurements were carried out using the following apparatus and conditions. Equipment: Mettler Toledo DSC-1 Sample container: Aluminum open cell Temperature range: 0~200℃ Heating / cooling rate: 2~40℃ / min Purge gas: N 2 Cooling method: Intracooler (electric cooling)
[0041] NC4, NC5, NC6, NC7, NC8, and NC9 produced above were each weighed out at 30 mg and dissolved in 6 ml of a 2:1 mixture of ethanol and chloroform. The obtained solution was left to stand in a dark place and recrystallized by slow evaporation. As another condition, the same solution was irradiated with UV (365 nm) at 20°C for 5 to 10 hours, and then recrystallized in a dark place by slow evaporation. The two types of crystals obtained were dried and weighed out at about 5 to 8 mg each in an open aluminum cell, and DSC was measured. The results are shown in Figure 3. In Figure 3, compounds (a) in which R has 4 to 9 carbon atoms correspond to NC4, NC5, NC6, NC7, NC8, and NC9, respectively.
[0042] As can be seen from Figure 3, the melting points of the examples NC4, NC5, NC6, NC7, NC8, and NC9 each dropped by a maximum of 38°C upon UV irradiation. It is believed that this difference in melting points caused melting due to isomerization in the crystals.
[0043] [Test Example 2] PCLT Test In the present invention, the PCLT test was carried out using the following apparatus and conditions. Equipment: Optical microscope OLYMPUS BX51 Temperature control system: Heat Stage Linkam THMS600 Temperature range: 0~150℃ Purge gas: N 2
[0044] The crystal pieces of S2C7, S4C7, and NC7 produced above were heated to 57.3℃, 54.7℃, and 118.5℃, respectively, on a heat stage, irradiated with UV (365 nm), and the changes in the crystals were observed under a microscope. The results are shown in Figure 4.
[0045] 4, it was found that, upon UV irradiation, S2C7 of the Example dissolved at 57.3°C, which is lower than the melting point (77.3°C), after 20 minutes, and NC7 of the Example dissolved at 118.5°C, which is lower than the melting point (138.5°C), after 2 minutes, while S4C7 of the Comparative Example did not dissolve even after 20 minutes at 54.7°C, which is lower than the melting point (74.7°C), even after UV irradiation. The acylhydrazone derivative of the present invention absorbed UV light, changed its molecular structure, and entered a high energy state, so it dissolved at a temperature lower than its melting point, indicating that light energy was stored.
[0046] [Test Example 3] Photoswitching test - NMR measurement In the present invention, NMR measurements were carried out using the following apparatus and conditions. Equipment: JEOL JNM-ECS400 spectrometer Solvent: DMSO-d 6
[0047] An appropriate amount of NC7 prepared above was dissolved in DMSO-d 6 A solution of NC7 was prepared by dissolving NC7 in 1000 ml of water. A solution of NC7 prepared in the same manner was irradiated with UV (365 nm) at 20°C for 2 hours to prepare a UV-irradiated solution. A solution of NC7 prepared in the same manner was heated at 130°C for 2 hours to prepare a heated solution. The NMR of these solutions was then measured. The results are shown in Figure 5.
[0048] From FIG. 5, it was found that the peak of N13-H present at the time of production of NC7 in the Example shifted in the PS state due to UV irradiation (365 nm), and the three-dimensional structure was changed. After that, when heated for 2 hours at 130°C, which is lower than the melting point of NC7 of 138.5°C, it melted, and the peak of N13-H returned to the position at the time of production, and the three-dimensional structure was found to be restored. It was shown that the acylhydrazone derivative of the present invention stores light energy by absorbing UV and changing the three-dimensional structure.
[0049] [Test Example 4] Photoswitching test - UV-Vis absorbance measurement In the present invention, the ultraviolet-visible absorbance measurement was carried out using the following apparatus and conditions. Equipment: JASCO V-630 spectrometer Solvent: DMSO-d 6 Concentration: 5.0×10 -5 M
[0050] A solution of NC7 and a UV-irradiated solution were prepared in the same manner as in Test Example 3, and the UV-visible absorption spectrum of each was measured. The results are shown in FIG.
[0051] As shown in Fig. 6, the maximum absorbance peak of NC7 in the example was 365 nm when it was produced, but disappeared in the PS state by UV irradiation (365 nm), indicating that the three-dimensional structure was changed. It was shown that the acylhydrazone derivative of the present invention absorbs UV and changes its three-dimensional structure.
[0052] [Test Example 5] Crystal structure analysis In the present invention, the analysis of the crystal structure was carried out using the following apparatus and conditions. Equipment: Rigaku XtaLAB P200 Temperature:93K
[0053] The NC7 (30 mg) produced above was dissolved in 6 ml of a 2:1 mixture of ethanol and chloroform. The resulting NC7 solution was either left as is or irradiated with UV (365 nm) for 2 hours, and then left in a dark place to be recrystallized by slow evaporation. The resulting crystals were subjected to X-ray crystallography. The results are shown in Figure 7.
[0054] As shown in Figure 7, when NC7 of the Example was recrystallized in the dark, (E)-isomer crystals were obtained, the conformation had a torsion angle of 39.6°, and a strong interaction was observed between CO and HN in the hydrogen bond network. When NC7 of the Example was recrystallized under UV irradiation, (Z)-isomer crystals were obtained, the conformation had a torsion angle of 59.9°, and a decrease in the bond was observed, and the hydrogen bond network was between NH and N and between CO and H. 3A weak interaction was observed between the acylhydrazone derivatives and CO. It was shown that the acylhydrazone derivatives of the present invention absorb UV light and change their conformation.
[0055] [Test Example 6] Observation of PCLT behavior In the present invention, the observation of the PCLT behavior was carried out by a PCLT test similar to Test Example 2. Equipment: Optical microscope OLYMPUS BX51 Temperature control system: Heat Stage Linkam THMS600 Temperature range: 0~150℃ Purge gas: N 2
[0056] The (E)-form crystal piece of NC7 produced above was placed on a heat stage and the temperature was set to the melting point of the (Z)-form crystal (111.1 °C). In this state, UV (365 nm) was irradiated and the PCLT of the (E)-form crystal was observed. The results are shown in Figure 8.
[0057] 8, it was found that the (E)-form crystals of NC7 of the Example melt at 111.1° C., which is the melting point of the (Z)-form crystals, when irradiated with UV (365 nm) for 150 seconds. This indicates that UV irradiation caused a transition from the (E)-form crystals, which have a melting point of 138.5° C., to the (Z)-form crystals, which have a melting point of 111.1° C. The acylhydrazone derivative of the present invention was shown to store light energy by absorbing UV and changing its three-dimensional structure.
[0058] [Test Example 7] DSC Measurements during Heating and Cooling Cycles (1) The (E)-form crystals of NC7 produced during production were irradiated with UV (365 nm) for 10 minutes at 111.1°C, which is the melting point of the (Z)-form crystals, to obtain a melt of the (Z)-form crystals of NC7. After this completely melted state was cooled to 20°C at a cooling rate of 5K / min, heating and cooling cycles were repeated and DSC was measured at a scanning rate of 5K / min in the same manner as in Test Example 1. The heating and cooling cycle was performed at a heating and cooling rate of 5K / min, with the first heating, the second cooling, and the second heating. The results are shown in Figure 9.
[0059] From FIG. 9, in the first heating, an exothermic peak (cold crystallization) of ΔH=-26.3 kJ / mol was observed, followed by an endothermic peak (melting) of ΔH=37.3 kJ / mol. In the subsequent first cooling, no endothermic peak was observed, confirming that the material was in a supercooled state. In the subsequent second heating, an exothermic peak (cold crystallization) of ΔH=-24.1 kJ / mol was observed, followed by an endothermic peak (melting) of ΔH=32.1 kJ / mol.
[0060] A schematic diagram of the results of Test Example 7 is shown in Figure 10. At 111.1°C, which is the melting point of the (Z)-form, the (E)-form crystals of NC7 were isomerized to the (Z)-form and melted by UV irradiation. The resulting (Z)-form melt was supercooled to 20°C at a cooling rate of 5 K / min to become a (Z)-form glass. When this glass was heated, heat was generated during the cold crystallization process. The (Z)-form crystals produced by this cold crystallization were heated and melted to become a (Z)-form melt.
[0061] [Test Example 8] DSC Measurements during Heating and Cooling Cycles (2) The NC7 (30 mg) produced above was dissolved in 6 ml of a 2:1 mixture of ethanol and chloroform. The resulting solution was left to stand in the dark and recrystallized by slow evaporation to obtain (E)-form crystals of NC7. The (E)-form crystals were measured by DSC in the same manner as in Test Example 1, at a scanning rate of 2 K / min. The heating and cooling cycle consisted of a first heating, a first cooling, a second heating, and finally a second cooling, all at a heating and cooling rate of 2 K / min. The results are shown in FIG. 11.
[0062] As can be seen from FIG. 11, an endothermic peak (melting) of ΔH=38.7 kJ / mol was observed in the first heating. In the subsequent first cooling, no peak indicating endothermic / exothermic reaction was observed, and it was confirmed that the material was in a supercooled state. In the subsequent second heating, a slight exothermic peak (cold crystallization) was observed, followed by an endothermic peak (melting). In the final second cooling, no peak indicating endothermic / exothermic reaction was observed, and it was confirmed that the material was in a supercooled state.
[0063] [Test Example 9] DSC Measurements during Heating and Cooling Cycles (3) The NC7 (30 mg) produced above was dissolved in 6 ml of a 2:1 mixture of ethanol and chloroform. The resulting solution was irradiated with UV (365 nm) for 2 hours, then left to stand in the dark and recrystallized by slow evaporation to obtain (Z)-form crystals of NC7. The (Z)-form crystals were subjected to DSC measurement in the same manner as in Test Example 1 at a scanning rate of 2 K / min. The heating and cooling cycle was carried out at a heating and cooling rate of 2 K / min, with the first heating, then the first cooling, followed by the second heating, and finally the second cooling. The results are shown in FIG. 12.
[0064] From FIG. 12, an endothermic peak (melting) of ΔH=36.3 kJ / mol was observed in the first heating. In the subsequent first cooling, no peak indicating endothermic heat generation was observed, and it was confirmed that the material was in a supercooled state. In the subsequent second heating, a slight endothermic peak (melting) was observed, followed by an endothermic peak (melting). In the final second cooling, no peak indicating endothermic heat generation was observed, and it was confirmed that the material was in a supercooled state.
[0065] In conventional latent heat storage materials, the absorption of heat (melting) during heating and the subsequent generation of heat (crystallization) are observed as a paired phenomenon. A special example of this is the "supercooling-cold crystallization type heat storage material" which does not crystallize during cooling, i.e., retains (stores) the absorbed heat during heating, and releases the stored heat the next time it is heated. As shown by the results of Test Examples 7 to 9, in the present invention, the material melts when irradiated with light, and the heat of fusion is provided by light energy, so there is no need to heat it. The molten liquid supercools without crystallizing during the cooling process, and releases the heat of crystallization when heated again, so the accumulated light energy can be released as thermal energy using heat as a trigger. [Industrial Applicability]
[0066] The acylhydrazone derivative of the present invention can be used as a heat storage material in heat exchangers that utilize light, and in systems that utilize light energy for living spaces (for example, air conditioning systems).
Claims
1. Formula (I): 【Chemistry 12】 (In the formula, R 1 and R 2 are hydrogen or, together with the carbon atoms to which they are attached, form a fused phenyl ring; R 3 is an alkyl group having 1 to 3 carbon atoms; R is an alkyl group having 1 to 9 carbon atoms or an alkenyl group having 2 to 10 carbon atoms, and these alkyl or alkenyl groups are unsubstituted or substituted with OH. An acylhydrazone derivative represented by the formula:
2. R 1 and R 2 The acylhydrazone derivative according to claim 1, wherein, together with the carbon atom to which they are attached, form a fused phenyl ring.
3. R 3 The acylhydrazone derivative according to claim 1, wherein is methyl.
4. 2. The acylhydrazone derivative according to claim 1, wherein R is a linear alkyl group having 4 to 9 carbon atoms.
5. A method for producing the acylhydrazone derivative according to any one of claims 1 to 4, comprising the steps of: Formula (II): 【Chemistry 13】 with a compound of formula (III): 【Chemistry 14】 in ethanol, methanol, 1-propanol, 2-propanol, or a mixture thereof to obtain a compound of formula (I): 【Chemistry 15】 (In the formula, R, R 1 , R 2 , and R 3 is as defined in any one of claims 1 to 4), A method comprising:
6. A heat storage material comprising the acylhydrazone derivative according to any one of claims 1 to 4.
7. A heat utilization system comprising the heat storage material according to claim 6.
8. 8. The heat utilization system according to claim 7, which is a residential light energy utilization system.